'There's a Starman waiting in the sky': Mourning David #Bowie on Twitter. (April 2019) - Van den Bulck, Hilde; Larsson, Anders Olof
This article analyses Twitter responses to the death of musician David Bowie as an inroad to a discussion about characteristics and functions of Twitter in the mediated relationships between celebrities, fans and the popular culture industry. The study focuses on questions regarding the nature of the Twitter community, types of emotions as well as expressions of fan creativity and the composition of online mourners. To this end, it provides a broad analysis of all tweets with #Bowie in the first 48 h after Bowie passed away ( N = 252, 318) and in-depth, quantitative and qualitative analysis of tweets with 100+ retweets ( N = 130). Results show high levels of retweeting and a limited number of tweets retweeted exceptionally often, suggesting a Twitter 'elite' leading the online mourning. This elite consists predominantly of media figures, celebrities, artists and music industry representatives rather than 'regular' individuals and fans, resulting in limited expressions of parasocial relationships. Besides being conduits of expressions of grief and information exchange, tweets focus on positive affirmation in tribute to Bowie's work. Results confirm that Twitter provides a virtual gathering of mourners who are (presumably) looking for recognition of loss and for expressions of support.